The therapeutic validity and effectiveness of physiotherapeutic exercise following total hip arthroplasty for osteoarthritis: A systematic review. - Annet Wijnen; Sjoukje E Bouma; Gesine H Seeber; Lucas H V van der Woude; Sjoerd K Bulstra; Djordje Lazovic; Martin Stevens; Inge van den Akker-Scheek (PLoS ONE, 2018)
Objective To assess the therapeutic validity and effectiveness of physiotherapeutic exercise interventions following total hip arthroplasty (THA) for osteoarthritis. Data sources The databases Embase, MEDLINE, Cochrane Library, CINAHL and AMED were searched from inception up to February 2017. Eligibility criteria Articles reporting results of randomized controlled trials in which physiotherapeutic exercise was compared with usual care or with a different type of physiotherapeutic exercise were included, with the applied interventions starting within six months after THA. Only articles written in English, German or Dutch were included. Study appraisal Therapeutic validity (using the CONTENT scale) and risk of bias (using both the PEDro scale and the Cochrane Collaboration's tool) were assessed by two researchers independently. Characteristics of the physiotherapeutic exercise interventions and results about joint and muscle function, functional performance and self-reported outcomes were extracted. Results Of the 1124 unique records retrieved, twenty articles were included. Only one article was considered to be of high therapeutic validity. Description and adequacy of patient selection were the least reported items. The majority of the articles was considered as having potentially high risk of bias, according to both assessment tools. The level of therapeutic validity did not correspond with the risk of bias scores. Because of the wide variety in characteristics of the physiotherapeutic exercise and control interventions, follow-up length and outcome measures, limited evidence was found on the effectiveness of physiotherapeutic exercise following THA. Conclusion The insufficient therapeutic validity and potentially high risk of bias in studies involving physiotherapeutic exercise interventions limit the ability to assess the effectiveness of these interventions following THA. Researchers are advised to take both quality scores into account when developing and reporting studies involving physiotherapeutic exercise. Uniformity in intervention characteristics and outcome measures is necessary to enhance the comparability of clinical outcomes between trials.